Correlation Analysis of the Need for Interactive Ethnographic Bumper Videos with Elementary School Students' Home Learning Activities - Deden Nur Fatahillah; Makmum Raharjo; Asawasulakin Asawasulakin (Journal of Educational Sciences, 2026)
This study explores the relationship between the need to develop interactive ethnographic bumper videos and the home learning process related to cultural learning at the elementary school level. The method adopted was descriptive quantitative, involving the participation of 330 students and 12 teachers from three elementary schools in South Sumatra. Data collection tools included six dimensions of needs (pedagogical, technical, cognitive, aesthetic, socio-cultural, and evaluative) and 20 indicators of home learning activities. Data collection was conducted through surveys, observations, and interviews, which were then analyzed using percentages and Spearman correlation analysis. The findings of this study indicate that all dimensions are in the high to very high category, with a significant correlation value between media needs in the school environment and home learning activities (rs = 0.70-0.75; p < 0.01). Aesthetic (88.1%) and cognitive (86.7%) aspects were identified as the main priorities in media development. These results emphasize that interactive ethnographic media has a significant role in integrating formal and non-formal learning experiences, as well as supporting the implementation of collaborative learning that is relevant to local culture. Practically, the results of this research form the basis for developing digital learning designs that focus on cultural values, theoretically, strengthening the concept.